International standards and recommended practices [relating to] the convention on international civil aviation (International Civil Aviation Organization MontrealCA, 1979)
Contains the following annexes. 1. Personnel licencing. 2. Rules of the air. 5. Units of measurements to be used in air and ground operations. 6. Operation of aircraft. 7. Aircraft nationality and registration marks. 8. Airworthiness of aircraft. 10. Aeronautical telecommunications. 14. Aerodromes. 15. Aeronautical information services. 17. Security. 18. The safe transport of dangerous goods by air. All annexes except number 17 contain supplements and ammendments.
IDS